Penerapan Pembelajaran Tematik Kelas V SDN 141 Pekanbaru - Tanti Junissa; Siti Quratul Ain (IJoIS: Indonesian Journal of Islamic Studies, 2022)
This researcher aims to describe how thematic learning planning, tthematic learning implementation, and thematic learning assessment at SDN 141 Pekanbaru. This researcher uses a case study approach. The subjects of this study were class teachers, principals, and students. The technique used by researchrs to collect data is to use the techniques of observation, interview, and documentation. Data were analyzed through data reducation, data presentation, and drawing conclusions. The technique of checking the validity of the data uses triangulation. And the results of the researchers showed that the teacher in preparing the lesson plans used steps such as choosing a theme, mapping the besics, reviewing the theacher’s book, reviewing the syllabus, then compiling the lesson plan. In the omplementation the teacher assesses three attitudes, namely arritudinal competence knowledge, and skilis.